2020
DOI: 10.1039/d0sc03528a
|View full text |Cite
|
Sign up to set email alerts
|

From CO2 activation to catalytic reduction: a metal-free approach

Abstract: Over exploitation of natural resources and human activities are relentlessly fueling the emission of CO2 in atmosphere. To address this issue of excessive CO2 emissions and its potential effects on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(11 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…While large-scale applications for CO 2 reduction require the use of “green” hydrogen, catalytic reductions using activated hydrides such as boranes or silanes are very useful as molecular probes to expand our knowledge in this field. Their structures inherently enable heterolytic activation pathways to deliver hydrides for the two-electron reduction together with an oxophilic counterpart . Examples that facilitate the transformation of CO 2 with such reducing agents to control the selectivity to two different reduction levels are shown in Figure A–C.…”
Section: Introductionmentioning
confidence: 99%
“…While large-scale applications for CO 2 reduction require the use of “green” hydrogen, catalytic reductions using activated hydrides such as boranes or silanes are very useful as molecular probes to expand our knowledge in this field. Their structures inherently enable heterolytic activation pathways to deliver hydrides for the two-electron reduction together with an oxophilic counterpart . Examples that facilitate the transformation of CO 2 with such reducing agents to control the selectivity to two different reduction levels are shown in Figure A–C.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide is one important contributor to the greenhouse effect, and its increasing emission from various sources triggers research of its capture and recycling into chemicals [1–13] . The use of CO 2 , which is non‐toxic and abundantly present in nature, as a C1 building block in chemical reaction systems is still not very common due to its high thermodynamic and kinetic stability [14] .…”
Section: Methodsmentioning
confidence: 99%
“…house effect, and its increasing emission from various sources triggers research of its capture and recycling into chemicals. [1][2][3][4][5][6][7][8][9][10][11][12][13] The use of CO 2 , which is non-toxic and abundantly present in nature, as a C1 building block in chemical reaction systems is still not very common due to its high thermodynamic and kinetic stability. [14] However, despite this, there are systems which are known to show reactivity towards CO 2 .…”
mentioning
confidence: 99%
“…CO 2 , with respect to its use as a source of carbon in catalytic processes has received massive attention, as the world is addressing issues in climate change, in particular with respect to hydrogenation. The reduction of CO 2 into value-added chemical products is considered to have the most potential for chemical transformation of CO 2 [6][7][8] . A group at Imperial Chemical Industries (ICI) in Billingham during the 1980s has shown that CO 2 plays an important role in methanol syntheses from CO/CO 2 /H 2 gas mixtures over a Cu/ZnO/Al 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%